Electrochromic polymer, preparation method and application thereof and high-performance fuchsin-transparent electrochromic film
Synthesis of electrochromic polymers by using cyclopenthiophene and 1,4-dialkoxybenzene in the field of electrochromicity and preparing high-performance magenta-transparent electrochromic films through spin coating technology, solving The problem of lack of high-performance magenta-transparent electrochromic materials in the prior art is achieved, and efficient transition from magenta to transparent color and good stability are achieved.
Patent Information
- Application Number
- CN202411340694.3
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-09-25
- Publication Date
- 2024-12-31
- Estimated Expiration
- 2044-09-25
AI Technical Summary
The lack of high-performance soluble magenta-transparent electrochromic materials in the prior art makes it difficult to achieve a magenta-transparent color change in the field of electrochromic.
Using cyclopenthiophene and 1,4-dialkoxybenzene as units, electrochromic polymers are synthesized by Suzuki reaction, and high-performance magenta-transparent electrochromic films are prepared through spin coating technology, using specific monomers Molar ratio and reaction conditions, controlling the structure and properties of the polymer.
The prepared film appears magenta in the neutral state and becomes transparent in the oxidation state, with an optical contrast of 56.4%, a coloring time of 0.7 s, a fading time of 0.6 s, and a contrast retained 84.3% after 1000 cycles. , exhibits good stability and performance.
Smart Images

Figure CN119219900A_ABST
Abstract
Description
Technical Field
[0001] The invention relates to the technical field of electrochromic materials, and in particular to an electrochromic polymer and a preparation method and application thereof, as well as a high-performance magenta-transparent electrochromic film. Background Art
[0002] In the field of electrochromism, color is the intuitive expression of materials and an important indicator for evaluating the performance of a material. We can adjust the structure of conductive polymers and then adjust their energy gap to obtain polymers of various colors. In recent years, researchers have made great efforts in designing and preparing soluble cyan, magenta and yellow (CMY system) electrochromic polymers with colored-transparent transition. Among them, many cyan and yellow electrochromic materials with excellent performance have been synthesized and reported, while soluble magenta-transparent electrochromic materials with high performance are rarely reported. Summary of the invention
[0003] The purpose of the present invention is to provide an electrochromic polymer and a preparation method and application thereof, as well as a high-performance magenta-transparent electrochromic film in view of the deficiencies in the prior art.
[0004] In order to achieve the above-mentioned object of the invention, the present invention provides the following technical solutions:
[0005] The present invention provides an electrochromic polymer, the structural formula of the electrochromic polymer is:
[0006]
[0007] R1 and R2 are independently one of C1-C30 alkane chains;
[0008] R3 and R4 are independently one of C1-C6 alkane chains;
[0009] n is an integer between 10 and 200.
[0010] The present invention also provides a method for preparing the electrochromic polymer, comprising the following steps:
[0011] Under a protective atmosphere, the first monomer, the second monomer, potassium carbonate, tetrakis(triphenylphosphine)palladium, N,N-dimethylformamide and water are mixed and reacted to obtain the electrochromic polymer;
[0012] The structural formula of the first monomer is: The structural formula of the second monomer is:
[0013]
[0014] R1 and R2 are independently one of C1-C30 alkane chains;
[0015] R3 and R4 are independently one of C1-C6 alkane chains.
[0016] Preferably, the molar ratio of the first monomer to the second monomer is 0.5-1.5:0.5-1.5;
[0017] The mass volume ratio of the first monomer, potassium carbonate, tetrakis(triphenylphosphine)palladium, N,N-dimethylformamide and water is 1 g: 1-4 g: 0.01-0.2 g: 30-45 mL: 10-15 mL.
[0018] Preferably, the reaction temperature is 110-130° C., and the reaction time is 16-20 h.
[0019] The present invention also provides the use of the electrochromic polymer in preparing a high-performance magenta-transparent electrochromic film.
[0020] The present invention also provides a method for preparing a high-performance magenta-transparent electrochromic film, comprising the following steps:
[0021] The electrochromic polymer is mixed with chloroform to obtain a polymer solution; the polymer solution is spin-coated on a conductive substrate to obtain the high-performance magenta-transparent electrochromic film.
[0022] Preferably, the mass concentration of the polymer solution is 5 to 20 mg / mL.
[0023] Preferably, the spin coating speed is 800-1200 r / s, and the spin coating time is 0.5-1.5 min.
[0024] The present invention also provides a high-performance magenta-transparent electrochromic film prepared by the preparation method of the high-performance magenta-transparent electrochromic film.
[0025] The present invention also provides application of the high-performance magenta-transparent electrochromic film in the field of electrochromism.
[0026] The beneficial effects of the present invention are:
[0027] The present invention uses cyclopentylbithiophene as the D unit and 1,4-dialkoxybenzene as the π unit, prepares an electrochromic polymer through Suzuki reaction, and successfully prepares a high-performance magenta-transparent electrochromic film by spin coating. The film prepared by the present invention exhibits magenta in a neutral state (0V) and is transparent in an oxidized state (1.1V), and has an optical contrast of 56.4% in a wavelength range of 532nm, a coloring time of 0.7s, a fading time of 0.6s, and a contrast retention of 84.3% after 1000 cycles. It is a new type of high-performance soluble magenta-transparent electrochromic material with great potential. BRIEF DESCRIPTION OF THE DRAWINGS
[0028] Figure 1 The cyclic voltammetry curves of the PCPDT-PhO film at different scanning speeds in Application Example 1 (Potential—voltage, Current—current);
[0029] Figure 2 The UV-visible absorption spectra (Wavelength—wavelength, Absorbance—absorbance) of the PCPDT-PhO film in Application Example 1 at different voltages;
[0030] Figure 3 Schematic diagram of the response time of the PCPDT-PhO film in Application Example 1 at 532nm (Time—time, Transmittance—transmittance);
[0031] Figure 4 Schematic diagram of the stability of the PCPDT-PhO film in Application Example 1 at 532 nm (Time—time, Transmittance—transmittance, retain 84.3% after 1000 cycles—the contrast retains 84.3% after 1000 cycles). DETAILED DESCRIPTION
[0032] The present invention provides an electrochromic polymer, the structural formula of the electrochromic polymer is:
[0033]
[0034] R1 and R2 are independently one of C1-C30 alkane chains;
[0035] R3 and R4 are independently one of C1-C6 alkane chains;
[0036] n is an integer of 10-200, preferably 15-150, more preferably 20-100, and further preferably 25-80.
[0037] The present invention also provides a method for preparing the electrochromic polymer, comprising the following steps:
[0038] Under a protective atmosphere, the first monomer, the second monomer, potassium carbonate, tetrakis(triphenylphosphine)palladium, N,N-dimethylformamide and water are mixed and reacted to obtain the electrochromic polymer;
[0039] The structural formula of the first monomer is: The structural formula of the second monomer is:
[0040]
[0041] R1 and R2 are independently one of C1-C30 alkane chains;
[0042] R3 and R4 are independently one of C1-C6 alkane chains.
[0043] In the present invention, the first monomer is prepared by conventional techniques in the art, and the preparation references are as follows: [RSC Adv. 2014, 4, 37738-37745], [Adv. Funct. Mater. 2012, 22, 2846-2854] and [Advanced Materials Research Vols 383-390 (2012) pp7677-7681]; the second monomer is purchased.
[0044] In the present invention, the protective atmosphere is preferably nitrogen.
[0045] In the present invention, the molar ratio of the first monomer to the second monomer is preferably 0.5-1.5:0.5-1.5, more preferably 0.7-1.3:0.7-1.3, and even more preferably 1:1.
[0046] In the present invention, the mass volume ratio of the first monomer, potassium carbonate, tetrakis(triphenylphosphine)palladium, N,N-dimethylformamide and water is preferably 1g:1-4g:0.01-0.2g:30-45mL:10-15mL, further preferably 1g:1.5-3.5g:0.05-0.15g:35-40mL:11-14mL, and more preferably 1g:2-3g:0.1-0.12g:37-38mL:12-13mL.
[0047] In the present invention, the reaction temperature is preferably 110-130°C, more preferably 115-125°C, and more preferably 120°C; the reaction time is preferably 16-20h, more preferably 17-19h, and more preferably 18h.
[0048] In the present invention, after the reaction is completed, the mixture is naturally cooled to room temperature, and the obtained mixture is post-treated to obtain the electrochromic polymer; the post-treatment preferably comprises the following steps: pouring the mixture into methanol, the volume ratio of the mixture to methanol is preferably 1:5-25, more preferably 1:10-20, and more preferably 1:15; filtering, drying the filter cake obtained by filtration, and after drying, Soxhlet extraction is performed with methanol, acetone, hexane and chloroform in sequence, the amount of methanol, acetone, hexane and chloroform is conventionally selected by a technician in this field according to the capacity of the Soxhlet extractor device, and finally collecting the polymer dissolved in the chloroform, spin-drying, and obtaining the electrochromic polymer.
[0049] The synthesis route of the electrochromic polymer in the present invention is as follows:
[0050]
[0051] The present invention also provides the use of the electrochromic polymer in preparing a high-performance magenta-transparent electrochromic film.
[0052] The present invention also provides a method for preparing a high-performance magenta-transparent electrochromic film, comprising the following steps:
[0053] The electrochromic polymer is mixed with chloroform to obtain a polymer solution; the polymer solution is spin-coated on a conductive substrate to obtain the high-performance magenta-transparent electrochromic film.
[0054] In the present invention, the mass concentration of the polymer solution is preferably 5 to 20 mg / mL, more preferably 10 to 15 mg / mL, and even more preferably 12 to 13 mg / mL.
[0055] In the present invention, the polymer solution is filtered through a Nylon 66 filter and then spin-coated on a conductive substrate; the pore size of the filter is preferably 20 to 24 μm, more preferably 21 to 23 μm, and more preferably 22 μm; and the conductive substrate is preferably ITO glass.
[0056] In the present invention, the spin coating rotation speed is preferably 800-1200 r / s, more preferably 900-1100 r / s, and more preferably 1000 r / s; the spin coating time is preferably 0.5-1.5 min, more preferably 0.7-1.3 min, and more preferably 1 min; after the spin coating is completed, it is naturally dried in the air to obtain the high-performance magenta-transparent electrochromic film.
[0057] The present invention also provides a high-performance magenta-transparent electrochromic film prepared by the preparation method of the high-performance magenta-transparent electrochromic film.
[0058] The present invention also provides application of the high-performance magenta-transparent electrochromic film in the field of electrochromism.
[0059] The technical solutions provided by the present invention are described in detail below in conjunction with the embodiments, but they should not be construed as limiting the protection scope of the present invention.
[0060] The second monomer in the embodiment of the present invention, 2,2'-(2,5-dimethoxy-1,4-phenylene)bis(4,4,5,5-tetramethyl-1,3,2-dioxaborolane, was purchased from Leyan, the website of which is https: / / www.leyan.com / 1338777-82-4.html.
[0061] Example 1
[0062] 1.00 g of cyclopentylbithiophene, 0.41 g of tetrabutylammonium iodide and 2.73 g of 1-Bromodecane was added to a 250 mL two-necked round-bottomed flask. Under nitrogen protection, 30 mL of a 50% sodium hydroxide solution was added, and the mixture was heated to 75°C for 6 h. After the reaction, the mixture was extracted with ethyl acetate (the volume ratio of ethyl acetate to the mixture was 1:3), and washed with saturated brine for 3 times. The volume ratio of saturated brine to ethyl acetate for each washing was 1:3. The organic layers were combined and dried with anhydrous sodium sulfate to obtain a sample. Silica gel with a particle size of 200-300 meshes and a mass of 1.3 times the mass of the sample was added, and the sample was concentrated and mixed under vacuum. Finally, petroleum ether was used as an eluent and 300-400 mesh silica gel was used as a stationary phase. The mixture was chromatographed to obtain a yellow-brown liquid (tested, the mass was 2.01 g, and the yield was 78%), namely 4,4-didecyl-4H-cyclopenta[2,1-b:3,4-b']dithiophene, with a structural formula of
[0063] The hydrogen spectrum data is: 1 H NMR (400MHz, CDCl3) δ7.14 (d, J = 4.8Hz, 1H), 6.93 (d, J = 4.9Hz, 1H), 1.87-1.76 (m, 2H), 1.36-0.80 (m, 19H).
[0064] 1.00 g of 4,4-didecyl-4H-cyclopenta[2,1-b:3,4-b']dithiophene was added to a 250 mL round-bottom flask, and then 60 mL of tetrahydrofuran was added. Under light-shielding conditions, 0.81 g of N-bromosuccinimide (added in 3 times, the mass ratio of the 3 times was 1:1:1), stirred at 25°C for 90 minutes, after the reaction was completed, the reaction solvent was removed by rotary evaporation, the mixture obtained by the reaction was extracted with dichloromethane (the volume ratio of dichloromethane to the mixture was 1:3), washed with saturated brine 3 times, the volume ratio of saturated brine used for each washing to the volume ratio of dichloromethane was 1:3, the organic layers were combined, dried with anhydrous sodium sulfate to obtain a sample, and silica gel with a particle size of 200-300 meshes was added with a mass 1.3 times the mass of the sample, concentrated and mixed under vacuum, finally, petroleum ether was used as an eluent and 300-400 mesh silica gel was used as a stationary phase, and a yellow liquid was obtained by chromatography (tested, the mass was 1.21 g, the yield was 92%), that is, 2,6-dibromo-4,4-didecyl-4H-cyclopenta[2,1-b:3,4-b']dithiophene, the structural formula is (first monomer);
[0065] The hydrogen spectrum data is: 1 H NMR (400MHz, CDCl3) δ6.92 (s, 1H), 1.79-1.71 (m, 2H), 1.37-0.80 (m, 19H).
[0066] 0.41 mmol 2,6-dibromo-4,4-didecyl-4H-cyclopentadien[2,1-b:3,4-b']dithiophene (0.25 g, first monomer), 0.41 mmol 2,2'-(2,5-dimethoxy-1,4-phenylene)bis(4,4,5,5-tetramethyl-1,3,2-dioxaborolane) (second monomer, structural formula ), 0.6g potassium carbonate, 0.04g tetrakis(triphenylphosphine)palladium were added to the reaction tube, under nitrogen protection, 7.5mL N,N-dimethylformamide and 2.5mL deionized water were added, the temperature was raised to 120°C, reflux was maintained for 18h, after the reaction was completed, it was naturally cooled to room temperature, the obtained mixture was poured into methanol (the volume ratio of the mixture to methanol was 1:15), filtered, and the filter cake obtained by filtration was dried. After drying, methanol, acetone, hexane and chloroform were used for Soxhlet extraction in turn, the polymer dissolved in chloroform was collected, and it was spin-dried to obtain an electrochromic polymer (tested, the mass was 0.22g, the yield was 86%), marked as PCPDT-PhO, with a structural formula of The value of n ranges from 25 to 80.
[0067] The hydrogen spectrum data of the electrochromic polymer obtained in this example are: 1 H NMR (400MHz, CDCl3) δ7.41(s,1H),7.28(s,1H),4.04(s,3H),2.03-1.81(m,2H),1.36-0.76(m,19H).
[0068] Application Example 1
[0069] 10 mg of the PCPDT-PhO prepared in Example 1 was added to a centrifuge tube, chloroform was added and ultrasonicated for 5 min to completely dissolve it, to obtain a polymer solution with a mass concentration of 10 mg / mL; after filtering the polymer solution with a Nylon66 filter (pore size of 22 μm), the polymer solution was spin-coated on an ITO glass (size of 0.9 cm*4 cm), the speed of the spin coater was set to 1000 r / s, the time was 1 min, and after the spin coating was completed, it was naturally dried in the air to obtain a high-performance magenta-transparent electrochromic film (marked as PCPDT-PhO film).
[0070] The PCPDT-PhO film was subjected to a performance test. Specifically, 1.935 g of tetrabutylammonium hexafluorophosphate was added to a 50 mL volumetric flask, and the volume was adjusted with 50 mL of acetonitrile. The flask was used as a blank solution. ITO glass with a PCPDT-PhO film on the surface was used as a working electrode, a platinum wire was used as a counter electrode, and an Ag / AgCl electrode was used as a reference electrode. The electrochromic performance was tested in conjunction with a UV-visible spectrophotometer. The electrochemical workstation was set to a cyclic voltammetry mode, the voltage range was set to 0-1.1 V, and the scan rates were set to 50 mV / s, 100 mV / s, 150 mV / s, 200 mV / s, 250 mV / s, 300 mV / s, and 350 mV / s. The cyclic voltammetry curves of the PCPDT-PhO film in Application Example 1 at different scan rates were obtained, as shown in FIG. Figure 1 As shown; the electrochemical workstation is set to constant potential mode, the voltage is set to increase from 0 to 1.1V, each time by 0.1V, and the voltage is applied continuously for 15s. The UV-visible absorption curve of the film at 350nm-1000nm at each voltage is recorded in situ using a UV-visible spectrophotometer to obtain the UV-visible absorption spectrum of the PCPDT-PhO film in Application Example 1 at different voltages, as shown in FIG. Figure 2 As shown; the electrochemical workstation is set to the voltage step mode, the step voltage is set to 0-1.1V, and the transmittance of the film at the maximum absorption wavelength of 532nm is tested using a UV-visible spectrophotometer to obtain a schematic diagram of the response time of the PCPDT-PhO film in Application Example 1 in the 532nm band, as shown Figure 3As shown; the electrochemical workstation is set to the voltage step mode, the step voltage is set to 0-1.1V, 1000 cycles are set, and the transmittance of the film at the maximum absorption wavelength of 532nm is tested using a UV-visible spectrophotometer. The stability diagram of the PCPDT-PhO film in the 532nm band in Application Example 1 is as shown in Figure 4 As shown. Figure 1 It can be seen that the initial oxidation potential of PCPDT-PhO is around 0.4V, showing a reversible redox peak, which reflects the good redox activity of PCPDT-PhO polymer and also brings stable redox properties to the polymer film. The peak current intensity of the polymer increases with the increase of the scan rate. Figure 2 It can be seen that in the neutral state of 0V, the polymer film is in a high light absorption state, with the maximum absorption peak at 532nm. As the voltage gradually increases, the intensity of the ground state absorption peak gradually weakens. When the voltage reaches 1.1V, the polymer film is in an oxidized state and exhibits a high transmittance in the visible light region (380-780nm). Figure 3 It can be seen that the optical contrast of the polymer at a wavelength of 532 nm is 56.4%, the coloring time is 0.7 s, and the fading time is 0.6 s. Figure 4 It can be seen that after 1000 cycles, the contrast retention is 84.3%, which is a very potential new type of soluble fuchsin-transparent high-performance electrochromic material.
[0071] As can be seen from the above examples, the present invention uses cyclopentylbithiophene as the D unit and 1,4-dialkoxybenzene as the π unit, prepares an electrochromic polymer through Suzuki reaction, and successfully prepares a high-performance magenta-transparent electrochromic film by spin coating. The film prepared by the present invention exhibits magenta in a neutral state (0V) and is transparent in an oxidized state (1.1V), and has an optical contrast of 56.4% in a wavelength range of 532nm, a coloring time of 0.7s, a fading time of 0.6s, and a contrast retention of 84.3% after 1000 cycles. It is a new type of high-performance soluble magenta-transparent electrochromic material with great potential.
[0072] The above is only a preferred embodiment of the present invention. It should be pointed out that, for ordinary technicians in this technical field, without departing from the principle of the present invention, several improvements and modifications can be made, such as adding some simple groups at the end of the alkyl chain that do not change the electrochromic properties of the original material. These improvements and modifications should also be regarded as the scope of protection of the present invention.
Claims
1. An electrochromic polymer, characterized in that The structural formula of the electrochromic polymer is: R1 and R2 are independently one of C1-C30 alkane chains; R3 and R4 are independently one of C1-C6 alkane chains; n is an integer between 10 and 200.
2. The method for preparing the electrochromic polymer according to claim 1, characterized in that: It includes the following steps: Under a protective atmosphere, the first monomer, the second monomer, potassium carbonate, tetrakis(triphenylphosphine)palladium, N,N-dimethylformamide and water are mixed and reacted to obtain the electrochromic polymer; The structural formula of the first monomer is: The structural formula of the second monomer is: R1 and R2 are independently one of C1-C30 alkane chains; R3 and R4 are independently one of C1-C6 alkane chains.
3. The method for preparing an electrochromic polymer according to claim 2, characterized in that: The molar ratio of the first monomer to the second monomer is 0.5-1.5:0.5-1.5; The mass volume ratio of the first monomer, potassium carbonate, tetrakis(triphenylphosphine)palladium, N,N-dimethylformamide and water is 1 g: 1-4 g: 0.01-0.2 g: 30-45 mL: 10-15 mL.
4. The method for preparing an electrochromic polymer according to claim 2 or 3, characterized in that: The reaction temperature is 110-130° C., and the reaction time is 16-20 hours.
5. Use of the electrochromic polymer according to claim 1 in preparing a high-performance magenta-transparent electrochromic film.
6. A method for preparing a high-performance magenta-transparent electrochromic film, characterized in that: It includes the following steps: The electrochromic polymer described in claim 1 is mixed with chloroform to obtain a polymer solution; the polymer solution is spin-coated on a conductive substrate to obtain the high-performance magenta-transparent electrochromic film.
7. The method for preparing a high-performance magenta-transparent electrochromic film according to claim 6, characterized in that: The mass concentration of the polymer solution is 5-20 mg / mL.
8. The method for preparing a high-performance magenta-transparent electrochromic film according to claim 6 or 7, characterized in that: The rotation speed of the spin coating is 800-1200 r / s, and the spin coating time is 0.5-1.5 min.
9. A high-performance magenta-transparent electrochromic film prepared by the method for preparing a high-performance magenta-transparent electrochromic film according to any one of claims 6 to 8.
10. Use of the high-performance magenta-transparent electrochromic film according to claim 9 in the field of electrochromism.
Citation Information
Patent Citations
Organic semiconductor material containing thiophene pyrrole dione unit and preparation method and application thereof
CN102443143A
Condensed ring thiophene type purple to transparent electrochromic polymer as well as preparation method and application thereof
CN115636926A
EDOT compound, preparation method thereof and application of EDOT compound in preparation of electrochromic material
CN116589485A
Production of electrochromic thin film
JP1991199388A
